2020
DOI: 10.1159/000504844
|View full text |Cite
|
Sign up to set email alerts
|

Association between Ankle Brachial Index, Brachial-Ankle Pulse Wave Velocity, and Mild Cognitive Impairment in Patients with Acute Lacunar Infarction

Abstract: Background: The link between arterial stiffness and mild cognitive impairment (MCI) is receiving increasing attention, and the goal of this study was to explore the relationship among the ankle brachial index (ABI), brachial-ankle pulse wave velocity (Ba-PWV), and MCI in patients with acute lacunar infarction (ALI). Methods: A total of 103 hospitalized patients with ALI were divided into a non-MCI group (n = 41) and an MCI group (n = 62) according to their Montreal Cognitive Assessment (MoCA) scores. A binary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…Evaluation of cognitive function after AIS was performed during the hospitalization in six studies 20 22 24 25 26 27 , and during follow-up after discharge in the other five studies 21 23 28 29 30 . Diagnosis of PSCI was based on the Mini-mental State Examination (MMSE) in two studies 20 28 , the Montreal Cognitive Assessment (MoCA) in seven studies 21 22 24 25 26 29 30 , and MMSE or MoCA in one study 27 . The other study reported two datasets of serum UA values for PSCI diagnosed with MMSE and MoCA, separately 23 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Evaluation of cognitive function after AIS was performed during the hospitalization in six studies 20 22 24 25 26 27 , and during follow-up after discharge in the other five studies 21 23 28 29 30 . Diagnosis of PSCI was based on the Mini-mental State Examination (MMSE) in two studies 20 28 , the Montreal Cognitive Assessment (MoCA) in seven studies 21 22 24 25 26 29 30 , and MMSE or MoCA in one study 27 . The other study reported two datasets of serum UA values for PSCI diagnosed with MMSE and MoCA, separately 23 .…”
Section: Resultsmentioning
confidence: 99%
“…UA after AIS may be associated with PSCI [19]. However, results of previous studies comparing the serum level of US between patients with and without PSCI showed inconsistent results [20][21][22][23][24][25][26][27][28][29][30], and the association between serum UA and PSCI in patients with AIS remains to be determined. Therefore, in this study, we performed a meta-analysis to systematically evaluate the association between serum UA and PSCI in patients with AIS.…”
Section: Uric Acid and Cognitive Impairment In Patients With Acute Is...mentioning
confidence: 99%
See 1 more Smart Citation
“…We speculated that ABI may be associated with brain tissue blood perfusion, and could be a good indicator of cognitive function in elderly hypertensive patients. Although many studies have reported the association between the ABI and cognitive function [11][12][13][14], few studies have focused on the relationship between the ABI and cognitive function in elderly hypertensive patients. Our cross-sectional study found that the ABI was associated with cognitive impairment independent of age, gender, education, ASCVD history, blood pressure related parameters (PP and PI), and baPWV, and the cohort follow-up study also con rmed that cognitive function declined more rapidly in patients with a low ABI, revealing an association between the ABI and cognitive function in elderly hypertensive patients.…”
Section: Discussionmentioning
confidence: 99%
“…[9,10] Studies have shown that the ABI could be a good indicator for cognitive impairment in community health population and patients with acute lacunar infarction or undergoing hemodialysis. [11][12][13][14] However, the relationship between ABI and cognitive function in elderly hypertensive patients has rarely been reported. According to the World Health Organization (WHO) age classi cation criteria for the elderly and the hypertension management guidelines, the elderly hypertensive patients can be divided into the young elderly hypertensive patients (60 ~ 75 years old) and the old elderly hypertensive patients (75 ~ 89 years old).…”
Section: Introductionmentioning
confidence: 99%